The Homily in The Eyes of The Youth: The Problem of Symmetry. A Sociological and Textual Analysis - Tomasz Adamczyk; Michał Klementowicz (Seminare, 2022)
The article discusses the category of symmetry. As a linguistic category, it is mainly studied in the context of ‘linguistic politeness.’ In textual studies, symmetry defines the shape of an utterance. In the process of communication, symmetry helps prevent differences between the subjects regarding their professional status, different social position or knowledge levels. The sociological studies (survey data from ca. 1 400 participants) show the urgent need to apply symmetry in homiletics as a response to various shortcomings of the process of exchanging thoughts during liturgy. Symmetry in sermons should be achieved in a twofold manner: 1. by maintaining the dialogical structure of the sermon; 2. by precisely defining the questio of the homily.